(untitled) (مجلة أبحاث قانونية, 2024)
As a result of the events that the world witnessed, starting with the global financial crisis in 2008 and passing through the Corona virus sweeping the world, and e-commerce occupying a prominent position, which has become a destination for many countries, Encrypted virtual currencies have emerged, which are based on the idea of breaking centralization and eliminating the role of banks as intermediaries between people. These encrypted currencies have become an issue imposed by reality after gaining acceptance by some individuals and companies despite the lack of legal and legal controls for them. Last year, in June 2023, Libya witnessed the discovery of a laboratory for mining encrypted virtual currencies(Bitcoin). This study aims to clarify the position of Islamic law, as well as the position of Libyan law on encrypted virtual currencies through the applicable legal texts, especially in the absence of an explicit text.